Business process improvement through e-collaboration : knowledge sharing through the use of virtual groups - Kock, Ned F., 1964- (Hershey PA : Idea Group Pub., 2005)
'This book focuses on business process improvement, a key element of the most influential management movement since the 1980s, and how process improvement affects organizational knowledge sharing'--Provided by publisher
Includes bibliographical references and index
Keywords: Reengineering (Management); Virtual work teams; Knowledge management; Organizational learning